Correlation Studies on Morphometric and Fodder Quality Traits in Bauhinia Variegata - Poonam; Thakur, I. K.; Sharma, J. P.; Singh, N. B. (Indian Forester, 2014)
Correlation studies were performed for progenies of thirty two plus tree on growth and fodder quality characterstics of Bauhinia variegata. A positive and highly significant correlation existed between basal diameter and number of branches (0.798), leaf area and lamina length (0.846). Significant and positive correlation was also observed between basal diameter and plant height (0.547), plant height and number of branches (0.520), highly significant and positive correlation existed between leaf fresh weight and leaf dry weight (0.984), phenotypic correlation coefficients were lower than their corresponding genotypic values. This could be either due to the modifying effect of environment or the strong inherent association of characters at genetic level. High significant and positive phenotypic (0.761) and genotypic (0.833) correlation existed between number of branches and basal diameter. Highly significant and positive genotypic and phenotypic correlations were observed between leaf fresh weight and leaf dry weight (0.989). Leaf fresh weight and leaf dry weight showed significant correlation with most of the morphometric traits. Simple correlation of morphometric traits with mineral nutrients were found non-significant. Genotypic correlation coefficients were found greater than phenotypic for most of the morphometric and leaf fodder traits.